Analysis of Comprehensive Edible Quality and Volatile Components in Different Varieties of Cooked Highland Barley - Caijiao Li; Jun Li; Wengang Zhang; Bin Dang; Xijuan Yang (Foods)
Twenty-two types of highland barley (HB) raw materials (including 10 common varieties and 5 main planting regions in the Qinghai province) were selected as the experimental materials to investigate their differences in the cooking characteristics, sensory quality, and characteristic flavor of cooked HB. The key volatile flavor components were identified using Gas Chromatography–Ion Mobility Spectroscopy (GC-IMS) combined with relative odor activity value (ROAV) analysis. The results indicated that the highland barley raw materials of Kunlun 15 (M5), Kunlun 14 (M9), Chaiqing 1 (M13) and Kunlun 14 (M14), and Chaiqing 1 (M20) and Kunlun 15 (M21) showed superior cooking quality, texture, and sensory scores. A total of 44 volatile flavor compounds were identified, including 16 aldehydes, 10 alcohols, 9 ketones, 7 esters, 1 acid, and 1 furan. Among these, 13 aldehydes, 4 alcohols, 4 ketones, 7 esters, and 1 furan were found across different cooked HB samples. Notably, ethyl, ethyl 2-methylbutanoate dimer, 2-methylbutanoic acid methyl ester, 2-butanone, 1-octen-3-ol, 1-pentanol dimer, and 2-pentyl furan contributed more significantly to the overall volatile profile. Cluster analysis combining principal component analysis revealed that Kunlun 16 (M16), Kunlun 17 (M17), Kunlun 14 (M18), Kunlun 15 (M19), as well as Chaiqing 1 (M20) and Kunlun 15 (M21), were the most suitable raw materials for cooking due to their better cooking quality, sensory attributes, and flavors, followed by Kunlun 15 (M10) and Kunlun 18 (M12), and Chaiqing 1 (M13) and Kunlun 14 (M14). These findings could help us identify specific HB varieties in corresponding regions with advantages, thus providing a theoretical basis for cooking HB.